Immune Profiling Reveals Molecular Classification and Characteristic in Urothelial Bladder Cancer - Yang, Li; Li, Aitian; Liu, Fengsen; Zhao, Qitai; Ji, Shaofei; Zhu, Wen; Yu, Weina; Zhang, Ru; Liu, Yaqing; Li, Wencai; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2021)
Urothelial bladder cancer (UBC) is the most common malignant tumor of the urinary system. Most patients do not benefit from treatment with immune checkpoint inhibitors, which are closely associated with immune profiling in the context of UBC. Therefore, we aimed to characterize the immune profile of UBC to identify different immune subtypes that may influence therapy choice. We identified four subtypes of UBC based on immune profiling including immune ignorant, cold tumor, immune inactive, and hot tumor. After excluding the cold tumor subtype because of its unique pathology distinct from the other types, a high correlation between patient survival and immune characteristics was observed. Most immune cell types had highly infiltrated the hot tumor subtype compared to other subtypes. Interestingly, although immune cells infiltrated the tumor microenvironment, they exhibited an exhaustion phenotype. CCL4 may be the key molecule functioning in immune cell infiltration in the hot tumor subtype. Moreover, neutrophils may function as an important suppressor in the tumor microenvironment of the immune ignorant and immune inactive subtypes. Furthermore, different tumor-intrinsic signaling pathways were involved in immune cell infiltration and exclusion in these four different subtypes. Immune profiling could serve as a prognostic biomarker for UBC, and has potential to guide treatment decisions in UBC. Targeting tumor-intrinsic signaling pathways may be a promising strategy to treat UBC.